Sea desabrido, camine con un bastón. Sobre tipos y estereotipos médicos en House - Guerra Gómez, Amparo (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
After introductory perspective on medical fiction in TV, the study analyses the impact on audiences of Dr. Gregory House character, as new doctor generation dealing with a disease image greatly influenced by forensic television.